»HOMINES PER HOMINES DISCUNT«: No Divine Revelation without Human Learning. Augustine's use of Scripture in the Prologue to De doctrina christiana - Koet, Bart J. 1955- (Jahrbuch für Antike und Christentum, 2018)
Is it possible that God communicates in dreams (see Num. 12,6)? The aim of this article is to assess how Augustine deals with the assertion in the Scriptures that God does communicate in dreams. In the prologue of De doctrina christiana Augustine adduces Paul, Peter, Philip and Moses as prime examples of persons who received special divine communication, but also as instances of an important Biblical dilemma: When and why is a divine communication trustworthy? In this prologue Augustine seems to accept the biblical stories about several forms of communications given by God, but also argues that by the sheer fact that they are presented in human language the divine communications turn into the object of human learning. Augustine stresses that no matter how privileged a divine revelation may be, a human teacher is still (or probably even: always) required to transmit it. His stress on the necessity of human learning as a kind of condition for wisdom, even for divine wisdom, is an example of his high esteem for the possibilities of human beings. Although a human teacher is important because without him there would be no handing over of divine revelation, Augustine does also mention that this knowledge is ultimately a gift of God.